Indian known as Tagish Charley hauling a sled of supplies with his dogs to Tagish, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: ""Tagish Charley" a noted Indian on his way to Tagish" Original photograph by Eric A. Hegg 687; copied by Webster and Stevens 257.A.